Landasan prinsip At-Ta’min: Fondasi Asas-asas keamanan finansial dalam Asuransi Syari’ah - Maulidina, Marissa Alifta; Abdilah, Ahmat Listrinto Maulana; Lubilii, Yodis; Fikri, Shofil (Maliki Interdisciplinary Journal, 2024)
Human life is surrounded by various kinds of threats that we don’t know when they will come. Humans need life insurance in the form of insurance. Therefore, we study insurance in order to understand the science of insurance as a provision for danger that we don’t know when it will come. The research method used in this article is a literature study method by reviewing research in compiling or making a clear discussion of the contents of the paper to be researched. This article discusses at-ta, min (insurance) in order to understand and explore, among other things: the meaning of insurance, the legal basis for insurance, types of insurance and the basic principles of insurance.